Aerodynamic design of an ultra-highly loaded booster of a high bypass ratio turbofan. (January 2019) - Chen, Yuwen; Zhou, Zhenggui; Cui, Cui
Based on an existing high bypass ratio turbofan, this paper uses a new concept of diffusion blade profiles with large camber and low flow losses to design a rotor for the booster, which characterizes the low wheel speed, thus achieving ultra-high loading of the rotor, effectively increasing its stage pressure ratio and reducing the weight of the booster. A booster with only one stage is designed by using the new blade profiles to replace the original booster with three stages. A two-dimensional design method of S1 (blade to blade)/S2 (hub to tip) stream surfaces is applied to design the blades of the rotor and the stator in the booster, and the two-dimensional blade profiles in the S1 stream surface are designed by means of an optimization design method. The flow fields in the original and newly designed boosters are simulated by using a numerical method. At the design point, the newly designed booster has nearly the same total pressure ratio and mass flow rate as the original booster and exhibits higher efficiency than the original booster. The surge margins of both boosters are nearly equal, and the newly designed booster can preferably match the original intermediate case.